The impact of social capital in achieving competitive priorities An applied study on Jordanian Islamic banks - Gahta, Asma (Finance and Business Economies Review, 2019)
This study aimed to know the effect of social capital (trust, peership, cooperation, and social integration) on achieving the competitive priorities (quality, cost, flexibility, delivery, time of service delivery, and excellence in the service) in the Jordanian Islamic banks. Study sample consisted of the Jordanian Islamic banks (Jordanian Islamic Bank, Arab International Islamic Bank and Jordan Dubai Islamic Bank). Al-Rajehi Bank was excluded because the study was limited to the Jordanian Islamic banks, and Al-Rajehi is unjordanian Islamic. The results also showed the presence of positive significant relation between the social capital variables (trust, peership, cooporation, and social integration), and the presence of a positive significant effect of these variables together on the competitive priorities.